Pengaruh Adat dalam Hukum Keluarga terhadap Pembaruan Hukum Nasional - Melani Diah Sekar Puri; Ridwan Arifin (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2019)
Indonesia as Unitary State consists of various kinds of tribes, customs, and even religions. The legal system adopted in Indonesia is not only civil or criminal law, but also mulually related religious and customary laws. Until recent years, Indonesia still uses European law as the national law and still try to make the customary law to be a national law. In fact, the implementation of European law is considered incompatible with the soul of the Indonesian people, especially in the the case family law. This paper seeks to uncover customary influences and effects in the development of family law in the national legal system.